РАЗЛИЧИЯ И СХОДСТВА ПРИЛАГАТЕЛЬНЫХ ЧЕРНЫЙ И БЕЛЫЙ В КАРАКАЛПАКСКОМ И АНГЛИЙСКОМ ЯЗЫКАХ - Джумамуратова, Г.Ж. (SCIENCE and SOCIETY, 2025)
This paper examines the importance of languages from a comparative perspective, which contributes to different practical uses not only of their structure, but also of their culturally specific features. Moreover, the role and place of the fragment of the linguo-color picture of the world, represented by the semantic opposition white/black and aq/qara within the framework of the cognitive-discursive paradigm, is clarified.